The Influence of Social Media Marketing on Purchase Decisions Mediated by Brand Equity and Brand Trust - Angelica, Marcella; Winoto Tj, Hery (AIBPM Publisher, 2024)
This research investigates the influence of social media marketing (SMM) on purchase decisions mediated by brand equity and brand trust. In this digital era, SMM has emerged as a critical strategy for businesses to engage consumers, specifically in the competitive fashion footwear market, such as PT Buccheri Indonesia. Using a quantitative approach, data were collected from 280 respondents domiciled in Jakarta, who had interacted with Buccheri’s Instagram account. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS software. The results reveal that: (1) SMM positively and significantly influenced brand equity, (2) SMM positively and significantly influenced brand trust, (3) SMM positively and significantly influenced purchase decision, (4) brand equity positively and significantly influenced purchase decision, (5) brand trust positively and significantly influenced purchase decision. Strengthening brand equity through brand awareness, perceived value, and brand loyalty, alongside building trust through consistent service, privacy protection, and fulfilling promises significantly impacts purchase decisions. This research highlights the role of SMM and provides actionable insights for Buccheri to optimize its SMM strategy by enhancing Instagram marketing content, reinforcing brand positioning, and converting digital interactions into tangible sales on Shopee